Advances in anti-inflammatory therapy for Livedoid vasculopathy - Dan HUANG; Sijian WEN (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2024)
Livedoid vasculopathy is a type of vascular disorder with unclear etiology and pathogenesis, in addition to the lack of standardized diagnostic and treatment guidelines. Currently, it is believed that the development of this disease is associated with blood hypercoagulability and inflammation. However, studies also suggest the involvement of immune and inflammatory reactions in its pathogenesis. And anti-inflammatory therapy is effective. The drugs used for the treatment of livedoid vasculopathy include plant alkaloids (colchicine, tripterygium glycosides), glucocorticoids, JAK inhibitors, adalimumab, intravenous immunoglobulins and anti-inflammatory drugs. This review aims to summarize the anti-inflammatory therapy and methods for livedoid vasculopathy, providing references for clinicians in the management of this disorder.